LEARNING SUCCESS IN THE LEARNING PROCESS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the success of assimilation in the educational process and the factors affecting it. Also, the use of new advanced, active teaching methods, and the use of rational tools to increase the effectiveness of educational work in higher education institutions are scientifically analyzed.